Terahertz sensing based on tunable fano resonance in graphene metamaterial - Wei Cui (Elsevier, 2021)
Here, the Fano resonance is investigated in a simple graphene metamaterial by the finite-difference time-domain (FDTD) method. The results indicate that transmission spectra of the Fano resonance can be tuned by the Fermi level and carrier mobility, and our proposed graphene metamaterial can be used in sensing applications at the terahertz band. Moreover, Figure of merit (FoM) for sensing can reach up to 106.92. Our proposal may pave the way for designing graphene-based terahertz sensing.